Enhanced warehouse layout planning to improve throughput efficency - Low, Jordan Jimmy Peng Seng. (2008)
This dissertation investigated the situation of a case study factory and the issues that arose due to inappropriate or outdated layouts that could no longer meet the new demand and requirements of the increased and huge volume of materials that flow through its factory. In order to analyze and understand the new requirements, it also studied the way the materials were procured and delivered to its stores.